(untitled) (Global Journal of Medical Research, 2022)
The foreign body in the maxillary sinus is quite a rare incidence. It may found in the case of maxillofacial trauma causing displacement of the tooth into maxillary sinus. The metallic foreign body may happen in case of gunshot injury and bullet, or pellet may retain in the maxillary sinus. Very rarely metallic foreign body like a dental burr may get lodged into maxillary sinus during dental procedure. If it happens ENT surgeon may be called upon to deal the foreign body. In this article we will describe a case that was referred to the ENT department, Khulna Medical College Hospital for removal of a dental burr retained in maxillary sinus. The accident happened in Dental department of the same hospital. We reviewed the options for the removal of the foreign body. There are two accepted approaches open and endoscopic for management of such cases. We successfully removed the foreign body through open approach.